Development and degradation analysis of novel three-layered sustainable composite coating for daytime radiative cooling - Bijarniya J.P.; Sarkar J.; Tiwari S.; Maiti P. (My University, 2025)
Structural stability, surface cleaning and wind speed effect, along with degradation behavior against sun exposure, dust deposition and water (rain) are important technical issues of daytime radiative cool coating for real-world application. Hence, we develop a three-layered coating consisting of an adhesive bottom layer (better stability), a middle layer of novel barium fluoride particle-based composite in PMMA polymer and a top protective cleanable PMMA layer for efficient daytime radiative cooling. Cooling performance is evaluated in terms of cooling flux and sub-ambient temperature drop. Performance degradation behavior of developed coating against sun exposure, water immersion and dust immersion is investigated. The effect of wind velocity on the radiative cooler performance is also evaluated experimentally. A temperature drop of nearly 3–5 °C is observed at the peak solar irradiance and a maximum temperature drop of approximately 7.2 °C is observed during afternoon hours. A maximum cooling power of 65 W/m2 is recorded experimentally in the afternoon. The negligible cooling performance degradation has been observed against sun, dust and water exposures, which confirms long-term sustainability. However, the significant effect of wind speed on cooling performance is observed for developed radiative coating (sub-ambient temperature drop is found to be inversely proportional to wind speed). © 2023 Elsevier B.V.